Evolution of sensory neuropathy after initiation of antiretroviral therapy - Centner, Chad (Division of Medical Microbiology, 2019)
Introduction: We studied the evolution of sensory neuropathy after antiretroviral therapy (ART) in human immunodeficiency virus–infected South Africans. Methods: Enrolment commenced before ART with 6-monthly follow-ups for 24 months. Symptomatic distal sensory polyneuropathy (SDSP) was defined as one symptom and sign. Symptom/sign scores were compared between visits. Results: We enrolled 184 participants. Pre-ART, 16% had SDSP. After 18 months of ART, pain prevalence decreased in those with pre-ART SDSP (odds ratio [OR], 0.09; 95% confidence interval [95%CI], 0.03-0.29). Symptoms improved in 50% ever experiencing pain (mean improvement=-4.5 on 11-point scale). Participants SDSP-free pre-ART developed SDSP at a rate of 18 per 100 person-years. After 24 months, 18% had SDSP. Stavudine (60% of cohort) did not predict incident SDSP, but associated with increased prevalence of reduced/absent reflexes at 18 months (OR, 2.24; 95% CI, 1.08-4.65). Conclusions: Painful symptoms improved during ART. Evolving sensory neuropathy was due to increasing small and large fiber dysfunction.